Reclaiming the Child Left Behind: The Case for Corporate Cultural Responsibility - Maon, François (Journal of business ethics, 2015)
Although a reasonable understanding of corporate social responsibility (CSR) exists, one dimension remains largely ignored. That is, the cultural impacts of corporations, or the bearing, at various levels of their business models, activities, and outcomes on the value systems and enduring beliefs of affected people. We introduce the notion of corporate cultural responsibility (CCR). The way corporations address CCR concerns can be reflected according to three stances: cultural destructiveness, cultural carelessness, and cultural prowess. Taken sequentially, they reflect a growing comprehension and increasingly active consideration of CCR concerns by corporations. In turn, we explicitly address issues related to the complex question of determining the cultural responsibilities of corporate actors; specify key CCR-related conceptualizations; and lay a foundation for discussions, debates, and research efforts centered on CCR concerns and rationales.